2011
DOI: 10.1007/s10897-011-9425-2
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Difficult News in a Cross‐cultural Setting: a Qualitative Study about Latina Mothers of Children with Down Syndrome

Abstract: Giving difficult news to patients represents a common dilemma for health care professionals. Based on three decades of research, various authors have proposed guidelines outlining the ideal setting, delivery, and timing. Existing publications focus on patients of European descent and may not be applicable in cross-cultural settings. We explored perceptions of Spanish-speaking mothers who have a child with Down syndrome and how they preferred to receive the news of their child's diagnosis. We conducted semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 18 publications
0
26
0
2
Order By: Relevance
“…Consequently, their perceptions of illness and health were influenced by different religions, norms and values. [35,45,48,95,[97][98][99][100][101][102][103][104][105] Patients who had a hierarchical worldview, for instance, were not used to reflecting on their own thoughts about illness, which made it difficult for them to answer some questions commonly asked by doctors. [38,106] Some patients used religious arguments to explain their condition.…”
Section: Differences In Cultural Perception Of Illness and Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, their perceptions of illness and health were influenced by different religions, norms and values. [35,45,48,95,[97][98][99][100][101][102][103][104][105] Patients who had a hierarchical worldview, for instance, were not used to reflecting on their own thoughts about illness, which made it difficult for them to answer some questions commonly asked by doctors. [38,106] Some patients used religious arguments to explain their condition.…”
Section: Differences In Cultural Perception Of Illness and Diseasementioning
confidence: 99%
“…For example, they replaced the cause of a disease with another etiology which was more in line with their religious beliefs. [100] The objectives that need to be reached to deal with these challenges were identified as knowledge and awareness of cultural differences, management of the patient's expectations of the health care system, mutual understanding [40,48,75,78,81,85,91,[107][108][109], and patient-centered care.…”
Section: Differences In Cultural Perception Of Illness and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Information support is consistently identified as a significant factor impacting parents' experiences of caring for their child with an intellectual disability (Willingham-Storr 2014). While recommendations suggest a need to provide substantial amounts of information to parents at the time of receiving a diagnosis of disability (Skotko et al 2009, Sheets et al 2011, the literature consistently reports that health professionals fail to provide enough current, comprehensive, accurate, balanced information about a child's condition and its implications for the child and family when informing parents of their child's diagnosis (Skotko 2005, Skotko & Bedia 2005, Gammons et al 2010, Choi et al 2011, Phelps et al 2012, Sheets et al 2012, Nelson Goff et al 2013, Willingham-Storr 2014, Goodwin et al 2015, Marshall et al 2015. Many parents therefore turn to peer support networks to assist them to understand their child's condition.…”
Section: Introductionmentioning
confidence: 99%
“…Information that helps parents to understand their infant's ongoing needs is also critical to facilitate parents’ advocacy for their infants to access crucial services (Adler et al., , Royal Australasian College of Physicians , p. 3). Despite this, research has shown that parents do not consistently receive enough accurate, relevant information about their infant's condition at the time of diagnosis and when it is provided, information is often outdated and negative (Choi, Lee, & Yoo, ; Gammons, Sooben, & Heslam, ; Goodwin et al., ; Marshall et al., ; Nelson Goff et al., ; Phelps, Pinter, Lollar, Medlen, & Bethell, ; Sheets, Baty, Vázquez, Carey, & Hobson, ; Skotko, ; Skotko & Bedia, ; Willingham‐Storr, ). Also, parents often lack the information they require to access relevant supports and services for their infant (Hussain & Tait, ; Marshall et al., ).…”
Section: Introductionmentioning
confidence: 99%